'n Ondersoek na die onderwysmetodiek van aanlyn fluitonderrig - Roux, Lerienne (2015)
ENGLISH ABSTRACT: Technological progress ensures the feasibility of distance music education. The physical absence of the educator raises unique challenges that require that the teaching methodology must be adapted. This thesis investigates the specific methodology changes that must be made in online flute tuition. A literature study was used to create a conceptual framework, which was consequently implemented in an iterative action research process. The unique contribution of this thesis is that it proposes a framework to flute educators for the presentation of online flute lessons.